Determination of the zeolite optimal diameter for the settlement of nitrifying bacteria in an aerobic bed fluidized reactor to eliminate ammonia nitrogen (2014)
In this work, the determination of the diameter of zeolite as a support for a microbial aerobic fluidized bed reactor is performed. The design of the reactor is recommended by Navarro and Palladino [1]. For the present study, the zeolite is crushed and classified granulometrically. Subsequently, the diameters of 0.5, 1 and 2 mm are arbitrarily chosen for the study of microbial adhesion. After the study of adherence of nitrifying bacteria, the obtained adhesion values for each diameter are not significantly different from each other. However, 1 mm is chosen to achieve higher adhesion values. Subsequently the aerobic fluidized bed reactor proposed by Navarro and Palladino [1] is built with the 1 mm-diameter zeolite. This presented an inlet flow of 1.35 mL.min-1 and a capacity of 8 L. The optimized quantity of zeolite for proper fluidization is 500 g, which is an 8% of total volume of the column. During operation, a good efficiency of reduction of the organic material is observed (50%).